2022
DOI: 10.1038/s41514-022-00084-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nicotinamide mononucleotide supplementation elevates blood nicotinamide adenine dinucleotide levels and alters muscle function in healthy older men

Abstract: Preclinical studies have revealed that the elevation of nicotinamide adenine dinucleotide (NAD + ) upon the administration of nicotinamide mononucleotide (NMN), an NAD + precursor, can mitigate aging-related disorders; however, human data on this are limited. We investigated whether the chronic oral supplementation of NMN can elevate blood NAD + levels and alter physiological dysfunctions in healthy older participants. We administered 250 mg NMN per day to aged men for 6 or 12 weeks in a placebo-controlled, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…Supplementation with NMN increases muscle insulin sensitivity, insulin signaling, and muscle remodeling in prediabetic women. 382 NMN prevents aging-related muscle dysfunctions 383 and shows benefits in improving aerobic capacity, cardiovascular fitness, sleep quality, fatigue, and physical performance. 89 , 384 As for NR, clinical trials indicate that NR suppresses inflammatory activation of PBMCs in heart failure patients 385 and decreases the levels of inflammatory cytokines in the serum and cerebrospinal fluid of Parkinson’s disease (PD) patients.…”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“…Supplementation with NMN increases muscle insulin sensitivity, insulin signaling, and muscle remodeling in prediabetic women. 382 NMN prevents aging-related muscle dysfunctions 383 and shows benefits in improving aerobic capacity, cardiovascular fitness, sleep quality, fatigue, and physical performance. 89 , 384 As for NR, clinical trials indicate that NR suppresses inflammatory activation of PBMCs in heart failure patients 385 and decreases the levels of inflammatory cytokines in the serum and cerebrospinal fluid of Parkinson’s disease (PD) patients.…”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“…A similar RCT reported that oral 300 mg/day NMN supplement was safe and significantly improved several blood biomarkers, such as HbA1c and HDL-C, but has significantly reduced blood NAD level for the 17 postmenopausal female participants after an 8-week trial [ 12 ]. A 12-week RCT with a fixed 250 mg/day oral NMN dose on 42 healthy older men showed that blood NAD concentration was significantly elevated and NMN was well tolerated, but NMN supplementation produced mixed results on skeletal muscle strength tests [ 13 ]. A separate RCT disclosed that, after intervention also with a fixed 250 mg/day NMN oral dose for 12 weeks on 30 healthy males and females, blood NAD concentration increased significantly starting at week 4 until the end of treatment at week 12 and returned to original level 4 weeks after NMN treatment, and the NMN supplementation was safe and well tolerated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We initially employed the MTS assay to measure the cytotoxicity of PM-conditioned medium (PCM) from PM-exposed KU812 cells, NMN or Q10, on HDFs. HDFs were treated with PCM for 8 h followed by 1 μM NMN or 100 nM Q10 for 16 h. The concentrations of NMN and Q10 use were based on previously reported studies [ 29 , 30 ]. Cell viability was expressed as a percentage compared to the control, which was treated with a supernatant collected from DMSO-stimulated KU812 cells.…”
Section: Resultsmentioning
confidence: 99%